Insights into the Enhanced Interfacial Stability Enabled by Electronic Conductor Layers in Solid‐State Li Batteries. Issue 10 (25th January 2023) - Luo, Linshan; Sun, Zhefei; Gao, Haowen; Lan, Chaofei; Huang, Xiaojuan; Han, Xiang; Su, Pengfei; Zhang, Zhiyong; Li, Cheng; Huang, Wei; Wei, Qiulong; Zhang, Qiaobao; et al.
Abstract: The (electro)chemical reactions between Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) solid‐state electrolyte and lithium metal plague the practical applications of LATP. A commonly used strategy to tackle this issue is to construct an ionic conductor layer to stabilize Li/LATP interface. Herein, it is demonstrated that an electronic conductor interlayer (Al or Ag) can also greatly enhance the interfacial stability of Li/LATP. To unveil the origin of the enhanced interfacial stability, a series of techniques, including in situ electron and optical microscopies, kelvin probe force microscopy, and finite element analysis, is exploited. Control experiments show clearly that Al layer can effectively homogenize the electric field distribution, which enables the uniform growth of interphases and thus prevents stress concentration and crack propagation. Moreover, when coupled with solid polymer electrolyte (SPE) to form Al‐SPE bilayer, it can effectively protect LATP from electron attack and interphase formation. Remarkably, Li symmetrical cells with an Al‐SPE bilayer exhibit superior stability of more than 5000 h at 0.2 mA cm −2, among the best cycling performances to date. This work presents an in‐depth understanding of the mechanism of the enhanced interfacial stability enabled by electronic conductor interlayers, as well as a universal interface architecture to boost the cyclability of solid‐state batteries. Abstract : The fundamental mechanism of enhanced interfacial stability of Li/Li1.3 Al0.3 Ti1.7 (PO4 )3 enabled by the electronic conductor interlayers is revealed. Compared to the inhibition of electron injection by an ionic conductor layer, which is widely accepted as the key role for stabilizing interfaces, this work emphasizes that the electric field homogenization caused by an electronic conductor layer is of equal importance.